Determinants of Social Interdependence and Interaction Among the Kanum Ethnic Group - Imelda C Laode; Fransin Kontu; Fitriani (Papsel Journal of Humanities and Policy, 2025)
This study aims to analyze the factors influencing the social interaction of the Kanum ethnic group as cross-border actors between the Sota area (Indonesia) and Waiber (Papua New Guinea). The Kanum people are indigenous communities residing on both sides of the border, sharing strong historical, cultural, and economic ties. The research was conducted in Kampung Sota, Sota District, Merauke Regency, South Papua Province, using a qualitative method with a descriptive approach and interactive model analysis by Miles, Huberman, and Saldana. The findings reveal that the key supporting factors for social interaction are mostly located in Sota-Indonesia, including better geographic access, infrastructure availability, border pass policy, favorable security conditions, and active economic and educational activities. On the other hand, the main hindering factors are found in Waiber-PNG, such as difficult geographic access, lack of infrastructure, limited governmental policies, and issues related to civil registration. Culturally and socially, the Kanum people experience no barriers due to shared values, traditions, and language. This study concludes that cross-border interdependence is not solely determined by national boundaries but also shaped by socio-cultural dynamics and inclusive policies. Keywords: Kanum ethnic, social interaction, cross-border, border, interdependence.